Autentusitas dan Gradualitas Al-qur'an - Amri Amri (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Muslim ummah claim that only the Qur’an is really authentic and gradual for its revelation. This claim is based on various verses of the Qur’an itself. The claim, although is considered saintific by all Muslims it is not accepted by non- Muslims. To make it more accepted scientificly by all believers (Muslims and non-Muslims), it needs to prove its authenticity and graduality of revelation through historical approach. In order to prove the originality of the Qur'an, the Muslims should not only use the evidence in the form of verse, but historical facts can not be denied by another Ummah. Therefore, describes Autensitas and Gradualitas Qur'an based on historical evidence is strengthened by the arguments of the Qur'an needs to be.